Authorea
DOI: 10.22541/au.157927292.26126702
|View full text |Cite
|
Sign up to set email alerts
|

Stock specific high-seas distribution of maturing sockeye salmon in the North Pacific

Abstract: The stock-specific distribution of maturing and adult salmon in the Northeast (NE) Pacific has been a persistent information gap that has prevented us from determining the ocean conditions experienced by individual stocks. This continues to impede understanding of the role of ocean conditions in stock-specific population dynamics. We assessed scale archives for 17 sockeye salmon (Oncorhynchus nerka) stocks covering the entire North Pacific, from the Columbia River to Kamchatka Peninsula, to define salmon locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The Suess effect itself, which result in lowering δ 13 C values for aqueous CO 2 , and the increase in aqueous CO 2 concentration, which allows phytoplankton to use more 12 C, their preferential isotope. The combination of these two mechanisms results in an exponential decrease of δ 13 C values at the base of the food webs, with the effect getting stronger in recent years (Espinasse et al, 2018). We correct our data using 2015 as a reference year.…”
Section: Isotopic Analysismentioning
confidence: 99%
“…The Suess effect itself, which result in lowering δ 13 C values for aqueous CO 2 , and the increase in aqueous CO 2 concentration, which allows phytoplankton to use more 12 C, their preferential isotope. The combination of these two mechanisms results in an exponential decrease of δ 13 C values at the base of the food webs, with the effect getting stronger in recent years (Espinasse et al, 2018). We correct our data using 2015 as a reference year.…”
Section: Isotopic Analysismentioning
confidence: 99%
“…More recently, Suchy et al (2022) found that early/late spring phytoplankton blooms (due to higher/ lower mean annual sea surface temperature) result in a mismatch with the phenology of larger crustacean zooplankton, resulting in lower overall crustacean biomass available for the higher trophic levels. The outcomes from these studies have highlighted how knowledge of regional patterns in ocean conditions is essential to understanding the response of regional fish stocks to changes in the pelagic ocean and the cumulative effects on species that migrate between different habitats (Espinasse et al, 2020;Shelton et al, 2021). In this context, delineating marine regions based on phytoplankton biomass patterns along BC and SEA's coastal oceans is of value in identifying their heterogeneity, defining pelagic habitats, and representing a baseline for assessing future changes.…”
Section: Introductionmentioning
confidence: 99%